CASSH Registry: Rationale and Study Design - Mohamad Ezzeldin; Ali Kerro; Ameer E. Hassan; Muhammad Shazam Hussain; Suhas V. V. Tatapudi; Rime Ezzeldin; Faheem G. Sheriff; Peter Kan; Chizoba Ezepue; Kaiz S. Asif; Ramesh Grandhi; Ali Alaraj; et al. (Stroke: Vascular and Interventional Neurology)
Background Carotid artery disease, a major cause of strokes, often results from carotid atherosclerotic stenosis. Although carotid endarterectomy has long been the standard treatment, carotid artery stenting (CAS) emerged as an alternative for high‐risk surgical patients. Operator experience plays a crucial role in reducing complications, with neurointerventional specialists demonstrating proficiency in CAS. However, they are often underrepresented in CAS studies. The CASSH (Carotid Artery Stenting Outcomes in Comprehensive Stroke Hospitals) registry aims to provide comprehensive insights into CAS outcomes, particularly when performed by neurointerventionalists at comprehensive stroke centers. Methods The CASSH is a multicenter, prospective, observational study currently enrolling patients with carotid artery stenosis undergoing CAS performed by neurointerventional physicians. All the participating sites will screen and report cases that meet inclusion criteria, on a monthly basis. The decision of whether to use CAS is at the discretion of the interventionalist. Results We will collect patients’ baseline clinical, demographic, and radiographic data. In addition, we plan to collect procedure variables and postoperative clinical and imaging data. Outcomes include the rate of postoperative symptomatic stroke (hemorrhagic/ischemic), access site complications, in‐stent thrombosis, and mortality. Conclusion Current literature underrepresents neurointerventionalists in CAS studies, especially as it pertains to procedural expertise and outcomes. CASSH is a prospective observational study that will enhance our understanding of CAS management and outcomes, emphasizing the benefits of neurointerventional expertise within comprehensive stroke centers.